A multilayer skin model for evaluating microneedle puncture performance and its preparation method and application

Electrospinning films are prepared by electrospinning technology and combined with commercial films to stack them on imitation subcutaneous tissue blocks to establish a multi-layer skin model, which solves the difficulties in evaluating microneedle puncture performance in the prior art and achieves higher accuracy and repeatability.

CN116080224BActive Publication Date: 2025-04-25WEIDI PHARM TECH (HANGZHOU) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310162857.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-24
Publication Date
2025-04-25
Estimated Expiration
2043-02-24

AI Technical Summary

Technical Problem

The prior art lacks a unified, scientific, easy to operate and easy to obtain method to evaluate the puncture performance of microneedles, resulting in difficulty in quality evaluation in the commercialization process of microneedles.

Method used

Electrospinning technology is used to prepare electrospinning films, and stack them on imitation subcutaneous tissue blocks alone or in combination with commercial films. Multi-layer skin models are established to determine their physical characteristics and puncture depth to evaluate the puncture performance of microneedles.

Benefits of technology

This method can more accurately simulate the physical characteristics of real skin, improve the accuracy and repeatability of microneedle puncture performance evaluation, and reduce the difference in reproducibility of experimental results.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116080224B_ABST
    Figure CN116080224B_ABST
Patent Text Reader

Abstract

The present invention relates to a multi-layer skin model for evaluating microneedle puncture performance and a preparation method and application thereof. The multi-layer skin model is obtained by stacking an electrospun membrane alone or in combination with a commercial film on an imitation subcutaneous tissue block. The spinning solution formula of the electrospun membrane is: PVA mass concentration accounts for 1-8%, PEG mass concentration accounts for 1-5%, DMF mass concentration accounts for 9-30%, and sucrose mass concentration accounts for 3%; the imitation subcutaneous tissue block is obtained by mixing silica gel and silicone oil in proportion. The present invention selects specific materials and a suitable technology to prepare a multi-layer skin model, which not only makes the model close to various physical properties of real skin and thus close to the effect of microneedle puncture of real skin, but also ensures the uniformity of the model and is convenient for counting the microneedle puncture depth.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of artificial simulated multi-layer skin models, and specifically relates to a multi-layer skin model for evaluating microneedle puncture performance, and a preparation method and application thereof. Background Art

[0002] Microneedles are an efficient, safe, and new transdermal drug delivery technology that has advantages that other traditional transdermal drug delivery technologies cannot achieve: microneedles make transdermal delivery of macromolecular drugs and hydrophilic drugs possible, achieving painless and minimally invasive drug delivery and improving patient compliance. Microneedle transdermal drug delivery technology has been widely studied and applied, among which polymer-soluble microneedles are more suitable for the delivery of biological products such as vaccines because of their degradability and good biocompatibility, but their mechanical strength is relatively weak, and the puncture performance of such products needs to be evaluated before they are developed and marketed. At present, the market demand for microneedle applications is broad and urgent, but the large-scale industrialization of this technology still faces certain difficulties. The lack of a unified, scientific, easy-to-operate, and readily available method for evaluating product quality is one of the main obstacles in the commercialization of microneedles.

[0003] The penetration depth is the most commonly used evaluation index in the evaluation of microneedle puncture performance, among which optical coherence tomography (OCT), tissue section method, paraffin film puncture method, etc. are mainly used to evaluate the penetration depth of microneedles. At present, the evaluation methods for studying microneedle puncture performance mostly use real skin. Because human skin is difficult to obtain, animal skin similar to human skin is mostly selected, such as mouse, rabbit, pig, etc. The poor uniformity of biological tissues has always been a major problem faced by the industry. The skin of different species and different parts of animals and their acquisition methods, their storage status (such as fresh, refrigerated, frozen or immersed in solution) and external factors (such as relative humidity and temperature) will affect the performance of the skin, resulting in poor reproducibility of experimental results. The thickness of the stratum corneum of human skin is about 10 to 25 μm, and the thickness of the stratum corneum of some tissues, such as the hands and feet, can reach several hundred microns; the thickness of the epidermis and dermis is greatly affected by the animal species, the thickness of the epidermis is generally between 70 and 120 μm, and the thickness of the dermis is 1 to 4 mm. The length of the microneedle is generally between 600 and 1200 μm. The actual length that can be penetrated during use is about two-thirds of the actual length. Therefore, the thickness of the skin model reaches about 1000 μm to meet the needs of microneedle puncture performance evaluation. Researchers found that paraffin film It has good uniformity, flexibility, ductility and color that is almost transparent and easy to observe. The researchers (LHERNOULD MS, DELEERS M, DELCHAMBRE A. Hollowpolymer microneedles array resistance and insertion tests[J]. Int J Pharm, 2015.) Eight layers of paraffin film are stacked to replace real skin. Each layer of paraffin film can fit tightly together. After microneedle puncture, clear holes can be left. The number of holes in each layer of paraffin film can be directly counted, and the penetration depth of microneedles can be reflected by a simple formula. Although this method is simple and convenient, and the distribution of the number of holes in each layer after microneedle array puncture can be observed, because the thickness of a single layer of paraffin film is as high as 127μm, and the paraffin film has high ductility, after the microneedle penetrates the paraffin film, the surrounding area of ​​the punctured hole in the upper layer will be extended to the next layer by the needle, resulting in low accuracy; and there may be a situation where the paraffin film is not punctured after the microneedle penetrates, and only the incision and indentation exist. Without the help of special instruments, it is impossible to accurately analyze and calculate the penetration depth of the incision or indentation by naked eyes. Therefore, when using paraffin film or similar film stacks to simulate skin to evaluate the penetration degree of microneedles in vitro, usually only the number of holes formed by the puncture of each film is counted. For a microneedle that is only a few hundred microns long, an error of more than 100 microns is unacceptable when calculating the penetration depth. In addition, real skin is hydrophilic, while paraffin film is hydrophobic, has strong plasticity, and cannot recover after stretching, which is quite different from the properties of real skin and cannot simulate the real situation of the skin. In addition, the source of paraffin film is monopolized by foreign companies, and there is currently no product from other companies that can replace it. The specifications are single and the cost of use is high. Therefore, it is urgent to find a method that is more suitable for evaluating the puncture performance of microneedles.

[0004] The artificial skin model complies with the 3R principle of "reduction", "replacement" and "optimization". It has the advantages of low preparation cost, strong operability, high uniformity, easy standardization and easy storage. It is a feasible route for evaluating the performance of microneedle puncture. According to the different characteristics and functions of the skin, many different types of skin models have been derived, including mechanical skin models, permeation skin models, tissue skin models and barrier skin models. Some researchers have used a self-made mechanical skin model to evaluate the puncture performance of microneedles. Some literature has proposed using Sylgard 184PDMS as the stratum corneum and TC-5005A / B / C PDMS as the epidermis. The mechanical skin model has low mechanical variability and high mechanical repeatability, which is convenient for observing the size of the puncture hole and can infer the penetration depth. However, PDMS is hydrophobic, which is not conducive to the evaluation of the puncture performance of soluble microneedles (RANAMUKHAARACHCHI SA, SCHNEIDER T, LEHNERT S, et al. Development and validation of an artificial mechanical skin model for the study of Interactions between skin and microneedles [J]. Macromol Mater Eng, 2016.). Other researchers have used silicone membranes to replace the stratum corneum, and polyether foam cotton / agar to replace the subepidermal tissue. The foam cotton / gel plays a supporting and shock-absorbing role for the silicone membrane; however, it cannot accurately simulate the properties of the skin (HU D L. The experimental research of insertion of microneedle and microneedle array into silicon membrane [D]. Da Lian; Dalian University of Technology, 2016.). None of these skin models meet the physical properties required for the evaluation of microneedle puncture performance. Therefore, it is urgent to establish an artificial skin model that is close to the physical properties of real skin and suitable for evaluating microneedle puncture performance.

[0005] Therefore, we proposed a solution to prepare a multi-layer skin model using a film with a thickness of only tens of microns. Among these films that meet the thickness requirements, commercially available films have undergone surface treatment, and after stacking, there will be gaps between layers and increased hardness, making them inappropriate and inaccurate for microneedle penetration depth evaluation. It is necessary to consider using specially made films, or a combination of them with commercially available films, to prepare a multi-layer skin model that is soluble in microneedle penetration depth evaluation.

[0006] Since human skin is mainly divided into the epidermis, dermis and subcutaneous tissue, each layer has different composition and thickness as well as variable mechanical response to stress. When the skin is loaded, the subcutaneous tissue bears the responsibility of load transfer and will undergo more deformation, which will affect the effect of microneedle puncture. At the same time, the subcutaneous tissue is also a necessary support for microneedle puncture of the skin. The design of simulated skin models also needs to consider support functions similar to fat, muscle, bone, etc., and the preparation of subcutaneous tissue blocks is also required. When using paraffin film, a thin film originally used as a sealing film, to simulate skin for in vitro puncture evaluation, no targeted scientific and technological analysis and research on the appropriate simulation of subcutaneous tissue by the corresponding support was conducted. Researchers arbitrarily used soft foam, rubber or other materials as supports according to their own understanding, judgment and conditions. It is impossible to unify or standardize the materials. The comparability of the research results is poor, which is not conducive to the standardization of microneedle performance evaluation. This is also a difficult problem that urgently needs to be improved when simulating skin in vitro for microneedle penetration evaluation. Usually the physical properties of the skin are characterized by thickness, elasticity, hardness, toughness, etc. We used the above parameters as the basis for establishing a practical skin model and carried out technical innovations based on the preparation of multi-layer films and subcutaneous tissue blocks to establish a multi-layer skin model that meets the requirements of simulating real skin.

[0007] In summary, choosing a suitable technology to prepare a thin film with a thickness of tens of microns and use it to prepare a multi-layer skin model can not only make the model close to the various physical properties of real skin and thus approach the effect of microneedle puncture of real skin, but also ensure the uniformity of the model and facilitate the statistics of microneedle puncture depth. This is a technical problem that technicians in this field urgently need to solve. Summary of the invention

[0008] The present invention provides a multi-layer skin model for evaluating microneedle puncture performance and a preparation method and application thereof; a film (electrospinning film) is prepared using electrospinning technology and is stacked alone or with a commercial film to establish a multi-layer skin model, and its physical properties and penetration depth are measured to find a film similar to skin tissue that can be used to evaluate the microneedle penetration depth, further optimize the prescription, improve the process flow, and prepare a multi-layer skin model that meets the requirements. The multi-layer skin model used in the present invention to evaluate the microneedle puncture performance not only allows the model to be close to the various physical properties of real skin and thus the effect of microneedle puncture of real skin, but also ensures the uniformity of the model, and can easily count the microneedle puncture depth, solving the shortcomings of the above-mentioned prior art.

[0009] To this end, the present invention has adopted the following technical solutions:

[0010] A multi-layer skin model for evaluating microneedle puncture performance, wherein the multi-layer skin model is obtained by stacking an electrospun membrane alone or in combination with a commercial film on an imitation subcutaneous tissue block, wherein the spinning solution formula of the electrospun membrane is as follows: PVA mass concentration accounts for 1-8%, PEG mass concentration accounts for 1-5%, DMF mass concentration accounts for 9-30%, and sucrose mass concentration accounts for 3%; the imitation subcutaneous tissue block is obtained by mixing silica gel and silicone oil.

[0011] Preferably, the commercial film includes OPP glass paper, lens cleaning paper, BOPP film, packaging wrapping film and Sydney paper.

[0012] Preferably, the spinning solution formulation of the electrospun membrane is: PVA concentration is 3%, PEG concentration is 3%, DMF concentration is 18.4%, sucrose concentration is 3%; the mass ratio of silica gel to silicone oil is 2:1.

[0013] Preferably, the thickness of the electrospun membrane is 10 to 35 μm, and the thickness of the commercial film is 10 to 50 μm.

[0014] A method for preparing a multilayer skin model for evaluating microneedle puncture performance comprises the following steps:

[0015] (1) Preparation of electrospun membrane

[0016] The spinning solution is prepared, mixed, loaded into a syringe, placed on the injection pump of the electrospinning instrument, the spinning parameters are adjusted, and dried after the spinning is completed; the spinning solution formula of the electrospinning membrane is: the mass concentration of PVA is 1-8%, the mass concentration of PEG is 1-5%, the mass concentration of DMF is 9-30%, and the mass concentration of sucrose is 3%;

[0017] (2) The electrospun membrane alone or in combination with a commercial film is stacked on a simulated subcutaneous tissue block to obtain a multi-layer skin model; the simulated subcutaneous tissue block is obtained by mixing silica gel and silicone oil.

[0018] Preferably, the spinning parameters include injection rate, voltage and spinning distance; the injection rate is 0.02-2 mL / h, the voltage is 10-30 kV, and the spinning distance is 5-15 cm.

[0019] Preferably, the injection rate is 1 mL / h, the voltage is 14 kV, and the spinning distance is 12.5 cm.

[0020] Preferably, the drying conditions include: room temperature drying, vacuum drying at 40°C, vacuum drying at 60°C, and air drying at 40°C.

[0021] The present invention also provides application of the multi-layer skin model in evaluating microneedle puncture depth and puncture quality.

[0022] Preferably, the multi-layer skin model is used to evaluate the puncture performance with higher accuracy and repeatability than paraffin film. The multi-layer skin model of the present invention is much better than paraffin film in terms of accuracy and standardization of use; compared with the length of the microneedle and the thickness of the paraffin film, the thickness of the electrospun membrane is small, and it is not easy for the microneedle to puncture the paraffin film without puncturing it, leaving only an indentation that is difficult to judge. It is convenient to judge the penetration depth of the microneedle according to the number of electrospun membrane layers punctured by the microneedle, so compared with the paraffin film, the multi-layer skin model has higher evaluation accuracy.

[0023] Compared with the prior art, the present invention has the following advantages:

[0024] The present invention selects specific materials and a suitable technology to prepare electrospun membranes and uses them to prepare multi-layer skin models, which not only allows the model to be close to the various physical properties of real skin and thus the effect of microneedle puncture of real skin, but also ensures the uniformity of the model and facilitates the statistics of microneedle puncture depth. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The appearance characteristics of commercial films are as follows: (a) OPP glass paper; (b) lens cleaning paper; (c) BOPP; (d) snow pear paper; (e) packaging wrapping film;

[0026] Figure 2 The appearance characteristics of eggshell membranes: (a) eggshell membranes after peeling; (b) the surface of eggshell membranes after stacking;

[0027] Figure 3 Schematic diagram of electrospinning equipment;

[0028] Figure 4 The appearance characteristics of the electrospun membranes are shown in Figure 2. (a) PVA; (b) PEG; (c) PVP;

[0029] Figure 5 Images of the puncture holes in different multi-layer skin models: (a) OPP glass paper; (b) lens cleaning paper; (c) BOPP; (d) snow pear paper; (e) packaging wrapping film; (f) eggshell membrane; (g) PVA electrospun membrane; (h) PEG electrospun membrane; (i) PVP electrospun membrane;

[0030] Figure 6 The appearance characteristics and morphology of the pierced holes of electrospun samples in different experimental groups, (a)-(g) are No.1-No.7;

[0031] Figure 7 This is a model diagram of the electrospinning device;

[0032] Figure 8 The graph is a graph showing the effect of different receiving distances on the electric field strength at 20 kV, (a) the electric field strength between the needle tip and the receiving device; (b) the electric field strength distribution on the receiving device;

[0033] Fig. 9 The graph of the electric field strength versus the needle voltage at a distance of 12.5 cm, (a) the electric field strength between the needle and the receiving device; (b) the electric field strength distribution on the receiving device;

[0034] Fig.10 The graphs are of thickness uniformity under different drying processes, (a) thickness difference before and after drying; (b) thickness after drying;

[0035] Fig.11 Schematic diagram of the preparation method of the microneedle negative mold;

[0036] Fig.12 The figure shows soluble microneedles with different spacings observed under a microscope;

[0037] Fig.13 It is a line graph of the results of two models of metal microneedle puncture (n=5);

[0038] Fig.14 It is a line graph of the results of two models of soluble microneedle puncture (n=5);

[0039] Fig.15 The penetration morphologies of microneedles into newborn pig skin, stacked paraffin films and multi-layer skin model; (a) pig skin; (b) paraffin film; (c) multi-layer skin model. DETAILED DESCRIPTION

[0040] The technical scheme of the present invention is further specifically described below through examples, which are provided for the purpose of explaining the present invention, not for limiting the present invention. Based on the examples in this application, all other examples obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0041] Main abbreviations and names

[0042] BOPP: biaxially oriented polypropylene

[0043] DMF: N,N-dimethylformamide

[0044] HPMC: hydroxypropyl methyl cellulose

[0045] LLDPE: linear low density polyethylene

[0046] MPa:mega pressure (megapascal)

[0047] N is for Newton

[0048] OCT: optical coherence tomography

[0049] OO:shore hardness unit

[0050] OPP: oriented polypropylene

[0051] PA:polyamide

[0052] PAA:polyacrylic acid

[0053] PDMS: polydimethylsiloxane

[0054] PE:polyethylene

[0055] PEG:polyethylene glycol

[0056] PET:polyethylene glycol terephthalate

[0057] PI:polyimide

[0058] PLGA: poly(lactic-co-glycolic acid)

[0059] PLLA: left-spin polylactic acid

[0060] PVA:polyvinyl alcohol

[0061] PVP: polyvinylpyrrolidone

[0062] RH stands for relative humidity.

[0063] rpm: rotations per minute

[0064] TPX:Transparent Polymer X(release film)

[0065] Example 1

[0066] 1.1 Material screening

[0067] Based on the design concept of the traditional paraffin film method, we screened more suitable materials to replace the paraffin film, and selected materials with physical properties similar to skin tissue from commercially available films (see Table 1), biofilms, cast membranes and electrospun membranes to establish a multi-layer skin model.

[0068] Table 1 Commercial films

[0069] name Composition and thickness OPP glass paper 30μm natural fiber and polypropylene commercial film BOPP film 18μm polypropylene granules commercial film PE film 20μm polyethylene commercial film PET film 50μm polyester commercial film TPU elastomer 100μm thermoplastic polyurethane elastomer PI film 50μm polyimide insulation film TPX release film 25μm poly (4-methylpentene) heat-resistant film PA film 20μm polyamide nylon film Graphite thermal conductive paper 50μm graphite thermal conductive paper Food Cellophane 23μm natural fiber commercial film Imide tape 50μm polyimide tape Packing Stretch Film 25μm LLDPE stretch film Lens cleaning paper 25μm cellulose paper Sydney Paper 18μm wood pulp copy paper

[0070] Preliminary experimental screening was conducted on commercially available film materials with a thickness of less than 100 μm, including BOPP film, PE film, TPU elastomer, PET film, PI film, TPX release film, PA film, graphite thermal conductive paper, OPP cellophane, food cellophane, imide tape, lens cleaning paper, packaging wrapping film, snow pear paper and other materials. After removing the harder materials, the screening index was used based on whether holes could be left after microneedle puncture, and finally OPP cellophane, lens cleaning paper, BOPP film, packaging wrapping film, and snow pear paper were selected for subsequent experiments. The preparation process of the commercial film is mature, the product quality control is good, and the flatness is high, such as Figure 1 As shown, the surfaces of OPP glass paper, BOPP and packaging wrapping film are smooth and flat, while lens paper and snow pear paper are made of pulp and have obvious fibrous surfaces, and the surface of snow pear paper is relatively wrinkled. The thickness of the selected commodity films is less than 100μm, among which the thickness of snow pear paper and packaging wrapping film is closest to the thickness of the skin stratum corneum. The toughness is from low to high in the order of OPP glass paper, lens paper, BOPP, snow pear paper, and packaging wrapping film; the toughness of BOPP film and packaging wrapping film exceeds 10N / mm, indicating that they have strong resistance to deformation by external force and are not easy to be torn; the toughness of OPP glass paper, lens paper and snow pear paper is below 5N / mm, and they are easy to break when torn, and have similar properties to the stratum corneum.

[0071] Various commercial films were stacked to 1000μm and placed on a silicone block simulating subcutaneous tissue. Their elasticity and hardness were measured as shown in Table 2: The elasticity of the multilayer skin model prepared by OPP glass paper and BOPP was similar to that of the silicone block simulating subcutaneous tissue. The elasticity of the multilayer skin model prepared by lens cleaning paper and snow pear paper was about 17kPa, which was lower than the elasticity value of the whole skin in the literature (20kPa-4MPa); the hardness of these five multilayer skin models was greater than 55OO, which was higher than the hardness value of the whole skin in the literature (20-50OO). Comprehensively considering various indicators, among which the single-layer snow pear paper had a lower flatness and could simulate the gully shape of the skin surface to a certain extent. Its thickness was 17.28±1.16μm and its toughness was 4.659±0.024N / mm, which was more in line with the properties of the skin stratum corneum; the elasticity of most of the multilayer skin models of various commercial films was lower than the theoretical value and the hardness was higher than the theoretical value, while the elasticity of the multilayer skin model prepared by BOPP was in line with the theoretical value and the hardness was the closest, which was the most in line with the requirements among these models. However, after the commercial films are stacked, the gaps between the layers are large and the hardness is high, which makes them inappropriate and inaccurate for microneedle puncture evaluation. It is necessary to find films that fit each other well and stack them to prepare a multi-layer skin model, which is also conducive to improving the shortcomings of high hardness.

[0072] Table 2 Appearance and mechanical properties of commercial films (n=6)

[0073]

[0074] 1.1.1 Biomembrane: Select eggs of appropriate size and peel off the eggshell membrane as the biomembrane material for screening test: ① Use tweezers to break the tip of the egg and pour out the contents; ② Use tweezers to gently break the blunt end of the eggshell, and when you see that there is no damaged eggshell membrane, gently expand the blunt end opening; ③ Add a small amount of clean water to the blunt end of the eggshell, shake it gently, and let the eggshell membrane separate from the eggshell by itself under the gravity of the water; ④ Continue to expand the blunt end opening of the eggshell until a complete and sufficient area of ​​eggshell membrane is exposed. The appearance characteristics of the eggshell membrane are as follows: Figure 2 As shown, the surface of the eggshell membrane is smooth ( Figure 2 -a), the surface is slimy and slippery, the thickness is 50.20±5.81μm, it is very easy to tear under stress, and its ability to resist deformation caused by external forces is poor. Its toughness cannot be measured. The eggshell membrane has a curved surface and cannot be completely flat. Figure 2 -b, after the eggshell membranes are stacked, the surface is undulating. After the eggshell membranes are stacked layer by layer to prepare a multi-layer skin model, the elasticity is measured to be 21.73±0.57 kPa and the hardness is 48.86±0.76OO, both within the theoretical value range of elasticity (20 kPa-4 MPa) and hardness (20-50OO).

[0075] 1.1.2 Casting film: Screen the film formation of different materials after drying. Carboxymethyl cellulose, sodium carboxymethyl cellulose, sodium alginate, carbomer 930, sodium polyacrylate NP-800, PAA-Na, phosphocellulose, β-cyclodextrin, D-trehalose, maltose, PVA224, PVPK30, poloxamer 188, PEG4000, sodium hyaluronate and other materials were used for screening. 5% mass fraction concentration was respectively configured in the sub-packaging bottles, and the total mass except the bottle body was 20g. It was fully dissolved in a water bath, opened in an oven to dry, and observed after film formation. Among them, sodium alginate, carbomer 930, sodium polyacrylate NP-800, PAA-Na, phosphocellulose, PVA224, poloxamer 188, sodium carboxymethyl cellulose, and sodium hyaluronate formed films, but the quality of the films was different. For example, the film of Carbomer 930 is not smooth, the film of PAA-Na has many bubbles, the film of phosphocellulose is layered, the film of Poloxamer 188 is cracked, and the conditions of the other films are shown in Table 3. The overall film formation time is long, and the properties of the formed film are not similar to the physical properties of the skin, which is not suitable for the preparation of a multi-layer skin model.

[0076] Table 3 Drying time and film formation of different materials

[0077] Material Film formation Sodium alginate Slightly hard, low brittleness, easy to tear Sodium polyacrylate NP-800 High toughness, not easy to tear, soft PVA224 Strong plasticity, can't be torn, no ductility, relatively soft Sodium Carboxymethyl Cellulose Strong plasticity, hard, no ductility, not easy to tear Sodium Hyaluronate Slightly hard in the middle, soft on both sides, plastic in the middle, tough around, not easy to tear

[0078] 1.1.3 Electrospun membrane screening

[0079] Considering that the gaps between layers of commercial films are large after stacking, and the hardness will increase, making it difficult to evaluate the puncture of microneedles, attempts were made to use homemade electrospun membranes alone or in combination with commercial films to solve the problems of large gaps and high hardness.

[0080] Electrostatic spinning is a special fiber manufacturing process. Under the action of a high-voltage electrostatic field of several thousand to tens of thousands of volts, the polymer droplets overcome the surface tension and produce a jet stream. The stream is stretched and solidified during the jetting process and falls on the receiving screen, eventually forming a non-woven, continuous mesh fiber mat. The basic equipment includes: a high-voltage power supply, a spinneret and a receiving device. Other accessories include micro pumps, syringes, etc. The experimental equipment is as follows: Figure 3 shown.

[0081] In the early stage, various polymers were formulated into solutions to prepare casting membranes. Polymer materials including PLLA, PLGA, chitosan, collagen, PVA, gelatin, PEG, etc. were preliminarily screened. According to film-forming properties, toughness, plasticity, hardness, and ductility, relatively excellent polymer materials were selected, and the concentration of spinnable materials was preliminarily explored. PVA, PEG, and PVP were selected as the main materials of electrospinning membranes for subsequent experiments.

[0082] ①.PVA-DMF electrospinning solution: The spinning solution contains 8% PVA, 18.4% DMF (N, N-dimethylformamide), and 3% sucrose. First, weigh the PVA powder in a beaker containing deionized water, stir it, and heat the beaker in a boiling water bath for about 2 hours. Stir continuously, cool it after it is fully dissolved, add DMF, and mix it. The spinning parameters are adjusted to a jet rate of 0.02mL / min, a voltage of 20kV, and a spinning distance of 15cm.

[0083] ②.PEG-DMF electrospinning solution: The spinning solution contains 8% PEG, 18.4% DMF, and 3% sucrose. First, weigh the PEG powder in a beaker containing deionized water, stir it, and heat the beaker in a boiling water bath for about 2 hours. Stir continuously, cool it after it is fully dissolved, add DMF, and mix it. The spinning parameters are adjusted to a jet rate of 0.4mL / min, a voltage of 11kV, and a spinning distance of 10cm.

[0084] ③.PVP-DMF electrospinning solution: The spinning solution contains 40% PVP, 18.4% DMF, and 3% sucrose. First, weigh the PVP powder in a beaker containing deionized water, stir it, and heat the beaker in a boiling water bath for about 2 hours. Stir continuously, cool it after it is fully dissolved, add DMF, and mix it. The spinning parameters are adjusted to a jet rate of 2mL / min, a voltage of 15kV, and a spinning distance of 11cm.

[0085] The above solutions were loaded into a 10 mL syringe, placed on the syringe pump of the electrospinning instrument, and the parameters were adjusted to set the temperature to 25°C and the humidity to 50% RH for electrospinning. The film thickness was adjusted by controlling the spinning time. After spinning, it was dried in a vacuum drying oven.

[0086] The appearance and mechanical properties of the films were evaluated and screened using the following indicators.

[0087] A. Flatness: Observe the surface morphology under a microscope and evaluate its flatness on a scale of 0-5. The higher the score, the flatter the surface.

[0088] B. Thickness: Use a spiral thickness gauge to measure the thickness of various films. Each sample is measured five times using the five-point sampling method and the average value is calculated.

[0089] C. Toughness: Toughness is measured in accordance with the national standard GB / T 16578.1-2008. A rectangular sample is cut in the center of each film along its length to form two legs, which are installed between the two fixtures of the universal testing machine. The legs are pulled in opposite directions by the fixtures and the force generated at the beginning of the cut is measured. Toughness is obtained by the following formula:

[0090]

[0091] Among them, σ is the tear strength of the sample, that is, toughness, in kN / m or N / mm; Ft is the average tear force, in N; d is the thickness of the sample, in mm.

[0092] D. Elasticity: The films were stacked to 1 cm and placed on a simulated subcutaneous tissue block. The model was placed on the platform of a universal testing machine and the compression mode was selected to measure the elasticity of the multi-layer skin model.

[0093] E. Hardness: Stack the films to 1 cm and place them on the simulated subcutaneous tissue module. Place the model on a flat table and measure its hardness with a hardness tester.

[0094] Various films were stacked and placed on a simulated subcutaneous tissue block. Metal microneedles were used to penetrate various multi-layer skin models at four levels of force. The number of holes in each layer was counted and the penetration depth was calculated according to the following formula:

[0095]

[0096] Where, d represents the penetration depth, μm; a represents the number of holes; and D represents the thickness of a single film, μm.

[0097] Hole clarity evaluation: - unclear, + clear, ++ very clear, take photos and record.

[0098] In the early stage, the spinnable concentrations of PVA, PEG and PVP were initially explored, and 8% PVA, 10% PEG and 40% PVP were selected for preliminary screening of the corresponding properties of electrospun membranes. Figure 4 As shown in the figure, the surface of the PVA electrospun membrane is dense and smooth. It is easy to leave fingerprints after touching. The surface is sticky and flocculent substances appear when sliding on the surface ( Figure 4 -a); PEG surface has clear fibers, smooth surface, not easy to wrinkle, and no stickiness ( Figure 4 -b); PVP has a sandy texture, is not flat and smooth, contains a lot of black impurities on the surface, and is easy to flocculent when touched ( Figure 4 -c).

[0099] The appearance characterization and mechanical properties of the electrospun membrane are shown in Table 4. When the rotation speed of the roller receiving device, the distance between the needle and the receiving device, and the swing amplitude of the needle remain unchanged, the thickness of the single-layer electrospun membrane is mainly determined by the volume of the electrospinning liquid ejected and the properties of the electrospinning liquid. Although the thicknesses of the three films are different, they all meet the requirements. PVP is similar to eggshell membrane and is easy to tear under stress, so its toughness cannot be measured. The toughness of PVA and PEG films is about 5N / mm.

[0100] Various electrospun membranes were stacked to 1000 μm and placed on a silicone block that simulated subcutaneous tissue. Their elasticity and hardness were measured as shown in the table: The elasticity of the multilayer skin models made with PVA and PEG were consistent with the theoretical values, while the hardness was slightly higher than the theoretical value, while the PVP multilayer skin model had lower elasticity and higher hardness.

[0101] Table 4 Appearance characterization and mechanical properties of electrospun membranes (n=6)

[0102]

[0103]

[0104] 1.1.4 Screening of subcutaneous tissue block materials

[0105] Dental wax sheets, polystyrene foam boards, gelatin, foam cotton, 0-degree silicone and other materials were screened for subcutaneous tissue blocks, and the elasticity and hardness of the above materials were measured. The skin elasticity measured in the literature was 20kPa-4 MPa, and the hardness was 20-50OO. The materials available on the market can also simulate subcutaneous tissue blocks. Among them, 0-degree silicone is often used as a simulation material for human tissue, and its elasticity and hardness are more consistent. The other materials have a certain gap, as shown in Table 5. Silicone oil can reduce the hardness of 0-degree silicone. By adjusting the different ratios of silicone and silicone oil, its elasticity and hardness are measured, and the results are shown in Table 6. Combined with the skin elasticity measured in the literature of 20kPa-4 MPa and hardness of 20-50OO, a prescription of silicone: silicone oil = 2:1 can be selected as a simulated subcutaneous tissue block to provide support for the multi-layer skin model.

[0106] Table 5 Results of elasticity and hardness determination of various materials

[0107] Material Elasticity / kPa Hardness / OO Dental wax 486.45±0.72 - Polystyrene foam board 635.49±0.68 - gelatin 3.83±0.60 7.25±0.46 Foam 568.47±0.51 - 0 degree silicone 34.92±0.79 61.16±0.44

[0108] Table 6 Determination of elasticity and hardness of 0 degree silicone and silicone oil mixed in different proportions (n=3)

[0109] No. The ratio of 0 degree silicone to silicone oil Elasticity / kPa Hardness / OO 1 Pure silica gel 34.92±0.79 61.16±0.44 2 Silicone: Silicone oil = 3:1 27.98±0.58 51.53±0.25 3 Silicone: Silicone oil = 2:1 26.88±0.52 47.32±0.33 4 Silicone: Silicone oil = 1:1 10.58±0.08 27.84±0.39

[0110] 1.2 Comparison of thin film materials

[0111] Our team conducted preliminary experiments and obtained a microneedle penetration depth range of 292.61-307.16μm as a reference for subsequent experiments. Various multi-layer skin models (multi-layer commercial films and homemade electrospun films were stacked on subcutaneous tissue blocks and fixed with a special clamp) were treated with 5×5 arrayed metal microneedles and the force applied by a microneedle-specific applicator. The pore morphology of the film surface was as follows Figure 5 As shown in Table 7, the probability penetration depth value was calculated according to the formula, and the hole clarity, average number of penetration layers and penetration depth of each skin model were recorded.

[0112] Table 7 Results of evaluating microneedle penetration depth in different multi-layer skin models (n=6)

[0113]

[0114] In summary, although the commercial film has mature technology, high quality control and high flatness, it cannot fully meet the requirements of simulating skin tissue, and the evaluated microneedle puncture depth is far lower than the theoretical value; the eggshell membrane is closer to the skin in terms of biological composition and structure, and the elasticity and hardness of the prepared multi-layer skin model meet the requirements, but the acquisition method is cumbersome, the eggshell membrane presents an arc, and cannot be completely flattened, which affects the puncture; the preparation time of the cast membrane is long, the quality control of the formed membrane is uneven, the overall plasticity is strong, and the microneedle penetration is difficult, which does not meet the needs of simulating skin tissue; although the preparation time of the electrospun membrane is long and cumbersome, the PVA film has better flatness, better mechanical properties, slightly higher hardness, clear microneedle puncture holes, and the microneedle penetration depth measured in the PVA multi-layer skin model exceeds the theoretical value range. Although the value measured in the PEG multi-layer skin model is far from the theoretical value range, PVA and PEG can be mixed to further optimize the spinning solution prescription to obtain a multi-layer skin model that meets the microneedle penetration requirements. At the same time, the combination of commercial film and electrospun membrane can meet the needs of simulating skin tissue and evaluating the performance of microneedle puncture. The multi-layer skin model specifically used in the present invention is composed of five layers of electrospun membranes stacked on one layer of commercial membranes stacked on five layers of electrospun membranes alternately stacked to 1000μm. The stacking method of the present invention is not limited to one type. It can be overlapped in sequence, or several layers of electrospun membranes can be stacked on several layers of commercial membranes, and any commercial membrane that meets the conditions can be used in one stacking process. This team's research found that when the piercing part contains an electrospun membrane, different stacking methods have little effect on the results.

[0115] Example 2

[0116] Optimization of spinning solution formulation for electrospinning

[0117] In order to obtain a multi-layer skin model that meets the requirements of microneedle penetration, PVA and PEG were combined in different solution proportions for experiments, and the effects of different concentrations of the spinning aid DMF on the preparation of electrospun membranes and the penetration depth of the multi-layer skin model were explored. The detailed experimental grouping is shown in Table 8, and the preparation of the spinning solution refers to Example 1. Sucrose, as a stabilizing excipient, can maintain the stability of the spinning solution and the long-term preservation of the electrospun membrane, and a 3% concentration of sucrose is used as the prescription.

[0118] Table 8 Spinning solution optimization grouping

[0119] No. PVA concentration ratio PEG concentration ratio DMF concentration ratio Sucrose concentration ratio 1 5% 1% 18.4% 3% 2 5% 3% 18.4% 3% 3 5% 5% 18.4% 3% 4 3% 3% 18.4% 3% 5 8% 3% 18.4% 3% 6 5% 3% 9.2% 3% 7 5% 3% 27.6% 3%

[0120] The electrospun membrane was characterized in appearance and evaluated for mechanical properties according to Example 1, and the penetration depth of the microneedles was evaluated.

[0121] Seven single-factor experimental groups were set up to explore the effects of PEG, PVA, and DMF concentrations on the quality of electrospun membranes. The appearance characteristics and mechanical properties of electrospun membranes in different experimental groups are shown in Table 9, the results of the multi-layer skin model to evaluate the microneedle penetration depth are shown in Table 10, and the appearance characteristics and penetration hole morphology of the electrospun membranes are shown in Table 11. Figure 6 .

[0122] Table 9 Appearance characterization and mechanical properties of electrospun membranes in different experimental groups (n=6)

[0123]

[0124] Table 10 Results of evaluating microneedle penetration depth in electrospun membrane multilayer skin model in different experimental groups (n=6)

[0125] No. Hole clarity Average penetration depth / μm 1 ++ 208.82±8.03 2 + 198.71±7.65 3 ++ 185.41±7.89 4 ++ 301.09±9.32 5 - 165.39±10.07 6 ++ 223.82±9.72 7 + 196.61±6.22

[0126] Based on these influencing factors and the results of the experimental groups, the lower the PEG concentration, the higher the penetration depth, and the lower the PVA and DMF concentrations, the higher the penetration depth. The penetration depth measured by prescription No. 4 has met the requirements, and its surface is flat and smooth, with moderate elasticity and only a high hardness. It can be combined with commercial films and stacked to simulate the skin.

[0127] OPP glass paper, lens cleaning paper, BOPP film, packaging wrapping film, and snow pear paper were selected and stacked with the film of No. 4 prescription to 1000 μm, and the composite film was characterized in appearance and evaluated for mechanical properties and the penetration depth of the microneedle with reference to Example 1. The surface of the composite film was flat and smooth, with moderate elasticity and hardness, and the penetration depth also met the requirements. The use of different stacking methods did not affect the overall physical properties and the evaluation of the microneedle puncture depth, and was very suitable for the evaluation of the microneedle puncture performance.

[0128] Example 3

[0129] Electrospinning process optimization

[0130] In order to ensure the uniformity of the electrospun membrane, the influence of the electric field distribution caused by different distances between the needle and the receiving device (spinning distance) on the electrospinning under different voltages was explored. Ansoft Maxwell 3D 21.0 was used to perform numerical simulation of the electrospinning device. Figure 7 The model shown includes a needle part and a receiving device, wherein the inner diameter of the needle is 0.15mm and the outer diameter is 0.3mm, and the receiving device is a cylinder with a length of 200mm and a diameter of 89mm. Both the needle and the receiving device are made of stainless steel. A voltage of 10 to 30kV is applied to the needle, and the receiving device is grounded with a voltage of 0V.

[0131] The needle voltage was set to 10kV, 15kV, 20kV, 25kV, and 30kV. The distance between the needle and the receiving device was set to 5cm, 7.5cm, 10cm, 12.5cm, 15cm, and vacuum. By exploring the effect of different distances between the needle and the receiving device on the electric field strength at the same voltage, it was found that the electric field strength distribution on the receiving device was the most uniform when the distance between the receiving device and the needle was 12.5cm. The effect of different receiving distances on the electric field strength at 20kV was as follows: Figure 8 As shown in the figure: (a) the electric field strength between the needle tip and the receiving device; (b) the electric field strength distribution on the receiving device. When simulating different voltages at the same distance, it was found that the voltage had no significant effect on the uniformity of the electric field strength, but only affected the magnitude of the electric field strength. At a distance of 12.5 cm, the electric field strength changes with the needle tip voltage as shown in the figure below. Fig. 9 Shown: (a) the electric field strength between the needle tip and the receiving device; (b) the electric field strength distribution on the receiving device.

[0132] The drying process was optimized with the optimal prescription, and different drying temperatures and environments were set for process optimization: room temperature drying, vacuum drying at 40°C, vacuum drying at 60°C, air drying at 40°C, and drying overnight. The thickness of the electrospun membrane determines the number of layers required to make a multi-layer skin model. The appropriate thickness can reduce the workload when spinning the membrane and calculating the penetration depth. Since the needle will swing left and right during spinning, the thickness of an electrospun membrane is uneven. At the same time, the drying process will affect the thickness of the electrospun membrane. In order to ensure the quality of its multi-layer skin model, the thickness uniformity of the electrospun membrane needs to be measured. The width of the silicone oil paper on the receiving device is 21cm. Using a thickness gauge, its thickness is measured every 1cm. The measured data is plotted into a statistical graph, and the position point with the highest thickness is found. The difference between the thickness of other positions and the highest thickness is calculated to obtain the position range where the thickness does not change, that is, the uniform thickness range.

[0133] Different drying processes were optimized and their thickness uniformity was analyzed. It was found that the electrospun membrane with the highest thickness uniformity range could be obtained by drying at 40°C with air blowing, with a thickness of 30.07±1.04μm, which was moderate and met the application requirements. The penetration depth of the microneedle measured by the optimized model was 302.09±3.58μm. The thickness uniformity under different drying processes was as follows Fig.10 Shown: (a) difference in thickness before and after drying; (b) thickness after drying.

[0134] In summary, in practical applications, when the spinning distance is set to 12.5 cm and the injection speed is 1 mL / h, the spinning is stable when the voltage is 14 kV, and the electrospun membrane with the highest thickness uniformity range can be obtained by drying at 40 °C with blowing air.

[0135] Example 4

[0136] Comparison with traditional paraffin film method to verify feasibility

[0137] Self-made metal microneedles were used, and the microneedle array area was 0.35 cm 2 , needle length 600μm, different spacings were designed as variables, and other parameters are as shown in Table 11:

[0138] Table 11 Microneedle size

[0139]

[0140]

[0141] Select the PDMS casting method to prepare the negative mold. The metal microneedle is used as the positive mold, and is placed on a small disc with a frame with the front side facing up. PDMS and curing agent are poured on the disc at a ratio of 10:1 to cover the positive mold. Vacuum for half an hour to remove bubbles, and then cure at 70℃ for 2 hours to obtain a PDMS negative mold. Fig.11 shown.

[0142] The one-step preparation method is adopted: the matrix solution is poured on the negative mold, centrifuged at 4000rpm for 18min, and demolded after drying to obtain soluble microneedles. Combining the toughness and brittleness theory of matrix materials with the previous prescription research, the matrix material and the proportion are prepared as follows: 26% Gantrez S-97, 6.5% HPMC, 67.5% water, and the microneedles that have been centrifuged into the mold are placed in a 40℃ oven overnight.

[0143] After demoulding, the appearance of the soluble microneedle was observed by microscopy. Fig.12 It can be seen that the needle body is clear and transparent, the shape is complete, the needle tip is sharp, the needle content is 100%, and it has a certain mechanical strength.

[0144] Soluble microneedles and metal microneedles with different spacings were punctured into traditional paraffin film and multilayer skin models (five layers of electrospun membranes stacked on one layer of commercial membranes stacked on five layers of electrospun membranes alternately stacked to 1000μm) stacked on simulated subcutaneous tissue blocks and fixed with special clamps using a microneedle exclusive applicator. After the penetration test of the traditional paraffin film and multilayer skin model, the penetration depth was calculated using a formula. The penetration depth results of the two methods were compared, and the microneedle parameters with better penetration effect were screened out.

[0145] like Fig.13As shown in the figure, the penetration depth of 5×5 array and 7×7 array on traditional paraffin film was significantly greater than that of multilayer skin model (p<0.01). When the number of microneedle arrays increased, the results of traditional paraffin film and multilayer skin model were closer. When the array was 10×10, the penetration depth value of multilayer skin model (157.07±4.96μm) was slightly higher than that of traditional paraffin film (156.82±3.69μm) but not significantly higher. This shows that when the spacing is large and the number of needles is small, the microneedle penetration depth is high. When the spacing becomes smaller and the number of needles becomes more, the microneedle is more difficult to penetrate. The two models for evaluating microneedle penetration are consistent in numerical trends. However, due to the high thickness and high ductility of the paraffin film itself, when the microneedle pierces the paraffin film, the pores will extend to the next layer, affecting the accurate calculation of the number of holes. The multilayer skin model has low thickness and moderate toughness, which can reduce the influence of the upper layer on the lower layer and improve the accuracy of calculating the penetration depth.

[0146] The results of penetration depth of soluble microneedles in traditional paraffin film and multi-layer skin models are as follows Fig.14 As shown in the figure, the evaluation results of the two models are similar, with no significant difference (p>0.05), but from a numerical point of view, the penetration depth of the traditional paraffin film of the microneedles with large evaluation spacing and small number of needles (5×5, 6×6) is slightly higher than that of the multi-layer skin model, while the penetration depth of the multi-layer skin model of the microneedles with large evaluation spacing and large number of needles (8×8, 10×10) is slightly higher than that of the traditional paraffin film. This trend is similar to that of metal microneedles. Because the mechanical strength of soluble microneedles is much lower than that of metal microneedles, the influence of microneedle spacing and needle number on the penetration depth is highlighted, which also reflects the higher accuracy of the multi-layer skin model. Similarly, considering comprehensively that the 5×5 and 6×6 arrays are more suitable for the puncture of soluble microneedles, large spacing and small number of needles can give priority to ensuring that the microneedles can penetrate effectively, and the penetration volume can be increased by increasing the length of the microneedles.

[0147] In summary, there is little difference in the results of penetration depth between the traditional paraffin film and the multi-layer skin model. The prepared multi-layer skin model can be used to evaluate the microneedle puncture performance. Moreover, the multi-layer skin model can overcome the defects of the paraffin film and improve the accuracy of calculating the penetration depth.

[0148] Example 5

[0149] Compare with real skin to verify feasibility

[0150] Pig skin is recognized by the industry as the animal skin that is closest to human skin. In the verification test, microneedles with a length of 1000 μm were inserted into the skin of newborn pigs, stacked paraffin films, and multi-layer skin models, respectively. The metal microneedles were inserted with a force of 5 N. The number of holes in each layer was counted and the microneedle insertion morphology was observed by referring to the method described in Item E of 1.1.3. of Example 1. The results are as follows: Fig.15As shown. Among them, as shown in Figure (a), in the pig skin, the microneedle penetrates most of the needle body, and only about 10% of the needle body does not penetrate into the pig skin. The paraffin film itself is used for sealing, and its own hydrophobicity and strong plasticity do not meet the puncture requirements of the microneedle. In addition, as shown in Figure (b), after the paraffin film is stacked, there are defects such as large gaps between layers and enhanced hardness, and the thickness of a single layer of paraffin film is too thick (127μm) and the ductility is high. After the microneedle penetrates the paraffin film, the surrounding area of ​​the punctured hole in the upper layer will be extended to the next layer by the needle, resulting in low accuracy; and there may be a situation where the paraffin film is not punctured after the microneedle penetrates, and there are only notches and imprints. Substituting it into the formula to calculate the penetration depth will result in an error value as high as 127μm, and the accuracy of measuring the microneedle puncture depth is low. The prepared electrospun membrane with uniform size and thickness is stacked with the commercial membrane in a "sandwich"-like manner, such as the stacking method in Figure (c), to form a multilayer skin model. It is not only close to the various physical properties of real skin, but also solves the defects of large gaps between layers and increased hardness after the paraffin film is stacked. The thickness of the single-layer electrospun membrane and the screened commercial membrane is about 30μm. Even if the membrane is not completely punctured, the error value when the formula is used to calculate the penetration depth is only 30μm, and the evaluation of the microneedle puncture depth is highly accurate. In addition, if the microneedle puncture direction is slightly inconsistent each time the puncture evaluation is performed, the number of layers of the paraffin film punctured may be different, and the repeatability of the evaluation using the paraffin film is poor; the advantage of the low single-layer thickness of the multilayer skin model is that it has good repeatability in the microneedle puncture evaluation.

[0151] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A multi-layer skin model for evaluating microneedle puncture performance, characterized in that: The multi-layer skin model is obtained by stacking an electrospun membrane alone or in combination with a commercial film on an imitation subcutaneous tissue block. The spinning solution formula of the electrospun membrane is as follows: PVA mass concentration accounts for 1-8%, PEG mass concentration accounts for 1-5%, DMF mass concentration accounts for 9-30%, and sucrose mass concentration accounts for 3%; the imitation subcutaneous tissue block is obtained by mixing silica gel and silicone oil; the commercial films include OPP glass paper, lens cleaning paper, BOPP film, packaging wrapping film and snow pear paper.

2. The multi-layer skin model for evaluating microneedle puncture performance according to claim 1, characterized in that: The spinning solution formula of the electrospun membrane is as follows: PVA concentration is 3%, PEG concentration is 3%, DMF concentration is 18.4%, sucrose concentration is 3%; the mass ratio of silica gel to silicone oil is 2:

1.

3. The multi-layer skin model for evaluating microneedle puncture performance according to claim 1, characterized in that: The thickness of the electrospun membrane is 10-35 μm, and the thickness of the commercial film is 10-50 μm.

4. A method for preparing a multilayer skin model for evaluating microneedle puncture performance, characterized in that The steps include: (1) Preparation of electrospun membrane The spinning solution is prepared, mixed, loaded into a syringe, placed on the injection pump of the electrospinning instrument, the spinning parameters are adjusted, and dried after the spinning is completed; the spinning solution formula of the electrospinning membrane is: the mass concentration of PVA is 1-8%, the mass concentration of PEG is 1-5%, the mass concentration of DMF is 9-30%, and the mass concentration of sucrose is 3%; (2) The electrospun membrane alone or in combination with a commercial film is stacked on a simulated subcutaneous tissue block to obtain a multilayer skin model; the simulated subcutaneous tissue block is obtained by mixing silicone and silicone oil; the commercial film includes OPP glass paper, lens cleaning paper, BOPP film, packaging wrapping film and snow pear paper.

5. The method for preparing a multi-layer skin model for evaluating microneedle puncture performance according to claim 4, characterized in that: The spinning parameters include injection rate, voltage and spinning distance; the injection rate is 0.02-2 mL / h, the voltage is 10-30 kV, and the spinning distance is 5-15 cm.

6. The method for preparing a multi-layer skin model for evaluating microneedle puncture performance according to claim 5, characterized in that: The injection rate was 1 mL / h, the voltage was 14 kV, and the spinning distance was 12.5 cm.

7. The method for preparing a multilayer skin model for evaluating microneedle puncture performance according to claim 5, characterized in that The drying conditions include: room temperature drying, vacuum drying at 40°C, vacuum drying at 60°C, and air drying at 40°C.

8. Use of the multi-layer skin model according to any one of claims 1 to 7 in evaluating microneedle puncture depth and puncture quality.

9. The use of the multi-layer skin model according to claim 8, characterized in that: The multi-layer skin model is used to evaluate the puncture performance with higher accuracy and repeatability than paraffin film.

Citation Information

Patent Citations

  • Soluble microneedle patch and preparation method thereof

    CN107412943A

  • In-vitro evaluation model for evaluation or quality inspection of microneedle transdermal drug delivery

    CN107942018A